2013
DOI: 10.1007/s11030-013-9450-1
|View full text |Cite
|
Sign up to set email alerts
|

A new and practical method for the synthesis of 6-aryl-5,6-dihydropyrido[2,3- $$d$$ d ]pyrimidine-4,7(3 $$H$$ H ,8 $$H$$ H )-diones

Abstract: A one step general synthetic methodology for the synthesis of 6-aryl-5,6-dihydropyrido[2,3-d]pyrimidine-4,7(3H,8H)-diones (17{[Formula: see text]} ([Formula: see text]) and 20{[Formula: see text]} ([Formula: see text])) is described. This methodology is based on reacting a 2-aryl-substituted acrylate (16{[Formula: see text]}) with the corresponding 6-aminopyrimidin-4(3[Formula: see text]-one (13 ([Formula: see text]; 19 ([Formula: see text])) in presence of a base under microwave irradiation. The resulting pyr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Abdolmalammad and Ballade synthesized a 7-amino-2,4-dioxo-5-aryl-1,2,3, tetrahydropyrido [2,3-d] pyrimidine-6-carbonitriles 7 by means of one pot simple, efficient method of multicomponent reaction using 6-aminouracil 5, propanedinitrile 2 and efficient heterogeneous catalyst (Scheme 2) (Abdolmohammadi & Balalaie, 2012a). Camarasa et al reported one-step method based on Michael addition reaction occurs between 6-aminopyrimidine-4 (3H) -ones 8 and substituted α, β-unsaturated aromatic esters 9 to produce a pyrido[2,3-d] Pyrimidine derivatives 10, in the presence of a base (K 2 CO 3 ) under microwave irradiation (Scheme 3) (Camarasa et al, 2013). Akbarzadeh et al discovered the simple, smooth and extremely competent one pot coupling reaction between 2,6-diaminopyrimidin-4 (3H) -one 8 and ethyl-2,4-dioxo-4phenylbutanoate derivatives 11 under reflux in DMF to produce novel ethyl-2-amino-3,4-dihydro-4-oxo-5phenyl pyrido[2,3-d]pyrimidine-7-carboxylatederivatives 12 (Scheme 4) (Ghaediet al, 2019).…”
Section: Methodologies For Pyridopyrimidine Scaffoldmentioning
confidence: 99%
“…Abdolmalammad and Ballade synthesized a 7-amino-2,4-dioxo-5-aryl-1,2,3, tetrahydropyrido [2,3-d] pyrimidine-6-carbonitriles 7 by means of one pot simple, efficient method of multicomponent reaction using 6-aminouracil 5, propanedinitrile 2 and efficient heterogeneous catalyst (Scheme 2) (Abdolmohammadi & Balalaie, 2012a). Camarasa et al reported one-step method based on Michael addition reaction occurs between 6-aminopyrimidine-4 (3H) -ones 8 and substituted α, β-unsaturated aromatic esters 9 to produce a pyrido[2,3-d] Pyrimidine derivatives 10, in the presence of a base (K 2 CO 3 ) under microwave irradiation (Scheme 3) (Camarasa et al, 2013). Akbarzadeh et al discovered the simple, smooth and extremely competent one pot coupling reaction between 2,6-diaminopyrimidin-4 (3H) -one 8 and ethyl-2,4-dioxo-4phenylbutanoate derivatives 11 under reflux in DMF to produce novel ethyl-2-amino-3,4-dihydro-4-oxo-5phenyl pyrido[2,3-d]pyrimidine-7-carboxylatederivatives 12 (Scheme 4) (Ghaediet al, 2019).…”
Section: Methodologies For Pyridopyrimidine Scaffoldmentioning
confidence: 99%
“…11 Compound 17 was obtained from methyl acrylate and 6-amino-2-(methylthio)pyrimidin-4(3H)one in 25% yield using an extension of the protocol described also by our group. 7 18 was obtained in 49% yield following the protocol described in Scheme 1, starting from methyl 2-(4fluorophenyl)acrylate. 5,6 Finally, compound 19 was obtained in 91% yield from 11a upon treatment with 10 equiv.…”
Section: •−mentioning
confidence: 99%
“…1), a scaffold for which we have described several straightforward synthetic strategies, allowing the decoration of all the five centers of diversity present in 1 . 1,5–7…”
Section: Introductionmentioning
confidence: 99%
“…Pyridodipyrimidine compounds include the motif of a pyridine fused to two pyrimidine rings, so researchers have to include the biological and synthetic applications of pyridines, pyrimidines, pyridopyridines and pyridopyrimidines, and pyrimidopyrimidines [ 107 120 ] on this type of compound in their future research. The formerly reported methods depend on the activity of different pyrimidine derivatives in their interactions with aldehyde derivatives and/or ammonium acetate to construct a pyridine ring.…”
Section: Future Prospectivementioning
confidence: 99%